Hubungan Massa Otot, Asupan Energi dan Protein Dengan Kekuatan Otot Tungkai Pada Atlet Sepak Bola - Permadi, M Rizal; Alist, Arifah Novi (JURNAL RISET GIZI, 2025)
Background: Leg muscle strength is important in soccer because all movements in the sport require leg muscle strength. Leg muscle strength is influenced by muscle mass, nutritional intake, age, and sex. Inadequate nutritional intake can disrupt an athlete's performance.Objective: This research aims to determine the relationship between muscle mass percentage and energy and protien intake with leg muscle strength among Pordes FC soccer athletes.Method: This study uses a cross-sectional research design. The subjects of this study were 25 Pordes FC soccer athletes from Kalisat, Jember Regency, aged 18-30 years, using total sampling techniques. Data on energy and protein intake were collected using the 2x24 hour food recall method, muscle mass was measured using BIA, and leg muscle strength was measured with the vertical jump test.Result:The analysis results for the variables of energy, protein, fat, and carbohydrate intake with leg muscle strength showed energy intake (p=0.000) and protein (p=0.001), indicating a significant relationship between energy, protein intake and leg muscle strength.Conclusion: The conclusion of this study is that there is a relationship between muscle mass percentage, energy and protein intake with leg muscle strength, in Pordes FC soccer athletes. Pordes FC athletes ought to diet based on their dietary requirements and choose high-quality protein sources.